Personalized Medicine in Cancer - Rahman, Md Mizanur (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Current and emerging biomedical science efforts are driven by determining how to improve clini-cal outcomes for patients. High-throughput tech-nology has revolutionized the area of transla-tional research, confirming the high complexity and heterogeneity of common diseases, partic-ularly cancer. Therefore, moving from classic single-gene-based molecular investigation to molecular network research might result in dis-covering clinical implications faster and more efficiently .Molecular characterization of tumour cells enables refinement of classifications for many cancers and can sometimes guide treatment. Malignant diseases are no longer classified only by tumour site and histology but are separated into various homogenous molecular subtypes, distinguished by a presumed key molecular alteration. Therapies for patients with cancer have changed gradually over the past decade, moving away from the administration of broadly acting cytotoxic drugs towards the use of more-specific therapies that are targeted to each tumour. To facilitate this shift, tests need to be developed to identify those individuals who require therapy and those who are most likely to benefit from certain therapies. In particular, tests that predict the clinical outcome for patients on the basis of the genes expressed by their tumours are likely to increasingly affect patient management, heralding a new era of personalized medicine. In this review a brief discussion on definition and molecular aspects of personalized medicine and its practical application for the management of common solid cancers are highlighted. J Bangladesh Coll Phys Surg 2014; 32: 153-163